1999
DOI: 10.1159/000023320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone and Dexamethasone plus Naltrexone on Pituitary Response to GnRH and TRH in Normal Women

Abstract: The hypothesis that glucocorticoids have a direct central inhibitory effect on the reproductive axis is sutained by the identification of glucocorticoid receptors on GnRH-secreting neurons and gonadotropic pituitary cells. It has been proposed that glucocorticoids and opioids interact centrally in the regulation of the GnRH-LH axis. The inhibitory effect of glucocorticoids may manifest not only directly through the hormone-receptor link, but also indirectly through an increase in opioid tone. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…(1999) also report a response of LH to GnRH after metformin therapy, similar to the basal test (before therapy), despite the reduction in insulin resistance. In a recent study (la Marca et al ., 1999) we demonstrated that oral administration of 2 mg dexamethasone in healthy women was followed by a reduction in the area under the curve of the LH response to GnRH. Glucocorticoids inhibit the GnRH‐LH axis, either directly, or indirectly through an increase in opioid tonus.…”
mentioning
confidence: 99%
“…(1999) also report a response of LH to GnRH after metformin therapy, similar to the basal test (before therapy), despite the reduction in insulin resistance. In a recent study (la Marca et al ., 1999) we demonstrated that oral administration of 2 mg dexamethasone in healthy women was followed by a reduction in the area under the curve of the LH response to GnRH. Glucocorticoids inhibit the GnRH‐LH axis, either directly, or indirectly through an increase in opioid tonus.…”
mentioning
confidence: 99%